Avaliação do processo de enriquecimento de farinha de trigo com apoio do controle de processos - Souza Neto, Floriano Soeiro de (2011)
Government policies in health are directed to preventive measures. In this respect, it was established in 2002 by the Brazilian Federal government, and also being controlled in several countries, that iron and folic acid must be added to wheat and corn flour. The aim of this research was to investigate the wheat flour enrichment process with folic acid. Were searched twenty-three among the largest flour mills in Rio Grande do Sul. Sixty (60) samples of wheat flour bought in supermarkets in the central region of the state of RS were also tested for the dosage of folic acid with HPLC. The tests were performed in laboratory of the Santa Maria Federal University. The variation in production methods and inadequate process control were salient. Only 18.3% of the samples studied were within the present regulatory measures. Thus, it was observed that the process, despite its importance, has low compliance.